The determinants of well-being among non-executive employees at TNB Kota Tinggi / Fatin Nur Ezzaty Zuraini - Zuraini, Fatin Nur Ezzaty (Faculty of Business and Management, 2019)
Employee well-being has become a common topic since it gives direct consequences for both individuals and organizations. Furthermore, it can affect to the performance of the employee as well as organization and lower the productivity. Therefore, this study aims to investigate the determinants of well-being among employees of TNB Kota Tinggi. This research was aimed to achieve the following objectives: investigate the relationship of job burnout and employees’ well-being at TNB Kota Tinggi; examine the relationship of psychological health and employees’ well-being at TNB Kota Tinggi; and determine the relationship of autonomy support and employees’ well-being at TNB Kota Tinggi. The total population of the research is 107 employees of TNB Kota Tinggi with sample size of 86 respondents. The researcher has used disproportionate stratified random sampling as sampling technique for this research. The questionnaire, measured on Likert scale was used to collect data from respondents. The questionnaire had Cronbach alpha of a= 0.924 which shown the instrument is reliable. Moreover, the results have shown that job burnout has not significant relationship with employees’ well-being. While, psychological health and autonomy support have positive and significant relationship with employees’ wellbeing. Therefore, the result will help the company to increase the employees’ wellbeing in order to increase performance and productivity.